The Effect of Digital Training and Digital Competencies on Employee Work Productivity at Bank Indonesia in Cirebon - Nita Dwi Andini; Editya Nurdiana (Journal Research of Social Science, Economics, and Management, 2026)
This study aimed to analyze the effects of digital training and digital competency on employee work productivity at Bank Indonesia Cirebon. Digital transformation in the banking sector requires human resource development to adapt to technology-based work systems. This study employed a quantitative associative approach using a survey method involving 60 respondents selected through a saturated sampling technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that digital training had a positive and significant effect on work productivity, with a path coefficient of 0.623 (p < 0.05). Digital competency also had a positive and significant effect on work productivity, with a path coefficient of 0.411 (p < 0.05). Simultaneously, both variables explained 66.2% of the variance in employee productivity. These findings indicated that improving the quality of digital training and strengthening digital competency were essential factors in enhancing employee effectiveness, efficiency, and performance in the digital transformation era. This study provides practical implications for organizations in developing structured and sustainable digital training programs to improve employee productivity.